The metastatic bone disease as a first clinical symptom in cancer - Wcisło, Gabriel; Korniluk, Jan; Leśniewski-Kmak, Krzysztof; Z. Pawlak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2002)
Bone is the third most common organ involved by cancer metastases. Breast, prostate, lung and renal cancers metastasize to bone most freqently. Most patients have bone metastases after previous diagnosis of cancer. However, few patients have metastatic bone disease as a first clinical manifestation in cancer. The paper will discuss diagnostic evaluation and therapeutic modalities in population of these patients. Patients with bone metastases in not diagnosed cancer most often present with pain as the principal symptom. The pain may be severe and tends to be worst at night. Some patients can present with the impending fractures, pathologic fractures, neurological abnormalities (e.g. related to spinal cord compression), hypercalcemia and bone marrow suppression at the beginning of disease. X-ray examination is the most specific test for these patients. Scintigraphy is excellent for use in bone metastases evaluation - this examination is very sensitive, but not very specific. In addition, complete blood cell count and biochemical serum panel should be assessed. The estimation of the risk of pathological fracture (metastases in appendicular skeleton) and spinal cord compression (metastases in axial skeleton) must be obtained. In the next step, myeloma must be included - especially, if multiple osteolytic areas are presented on plain radiographs. After differential diagnosis (myeloma or other primary bone tumour or cancer metastases) identify the primary site of disease must be performed. In this aim, following tests can be used: tumour markers (e.g. CA-125, CA 15-3, CEA, PSA), chest radiography and computer tomography, mammography, prostate ultrasound examination, abdomen and pelvis computer tomography or magnetic resonance imaging. Finally, histopatological or cyological diagnosis must be obtained. Treatment of patients due to bone metastases as first clinical symptom in cancer is similar to others with metastatic bone disease. There is the multimodality approach in these patients, including local (surgery and radiation) and systemic therapies - chemotherapy, hormone and immune therapies, and bisphosphonates. Quick diagnosis and adequate therapy should be the goal, to maintain patients' quality of live and functional level.